Prevalence of low bone mass among adolescents with nontransfusion‐dependent hemoglobin E/β‐thalassemia and its relationship with anemia severity. Issue 1 (12th August 2017) - Nakavachara, Pairunyar; Petchkul, Jaturat; Jeerawongpanich, Krittha; Kiattisakthavee, Pornpimol; Manpayak, Teerarat; Netsakulnee, Parichat; Chaichanwattanakul, Katharee; Pooliam, Julaporn; Srichairatanakool, Somdet; Viprakasit, Vip
Abstract: Background: Low bone mass is common among adolescents with transfusion‐dependent β‐thalassemia despite adequate transfusion and iron chelation. However, there are few reports regarding bone mineral density (BMD) among adolescents with nontransfusion‐dependent thalassemia (NTDT). Indeed, only BMD data in patients with nontransfusion‐dependent (NTD) β‐thalassemia intermedia have been reported. No previous study has investigated BMD among adolescents with NTD hemoglobin (Hb) E/β‐thalassemia. Objective: To determine the prevalence of low bone mass among adolescents with NTD Hb E/β‐thalassemia and factors relating to low bone mass. Methods: We investigated BMD of lumbar spine (L2–L4; BMDLS) and total body (BMDTB), as measured by dual‐energy X‐ray absorptiometry, in 22 adolescents (aged 13.2–20 years) with NTD Hb E/β‐thalassemia. Results: Low bone mass was found to be 18.2% and 22.7% at the lumbar spine (BMDLS Z‐score adjusted for bone age and height age) and 13.6% and 9.1% at the total body (BMDTB Z‐score adjusted for bone age and height age). Patients with mean Hb level <8 g/dl were more likely to have low bone mass (BMDLS and BMDTB Z‐scores adjusted for bone age) compared to those with Hb level ≥ 8 g/dl. Mean Hb level correlated with BMDLS and BMDTB Z‐scores adjusted for bone age. Conclusion: We demonstrated that a low Hb level was associated with low bone mass among adolescents with NTD Hb E/β‐thalassemia. A significant proportion of low bone mass among these patients highlights the importance of appropriate management, including red cell transfusion, vitamin D and calcium supplementation for improved long‐term bone health.